Reconstruction design before tumour resection: A new concept of through-and-through cheek defect reconstruction. (November 2017) - Gong, Zhao-Jiang; Ren, Zhen-Hu; Wang, Kai; Tan, Hong-Yu; Zhang, Sheng; Wu, Han-Jiang
Highlights: This study provides a new concept of through-and-through cheek defects reconstruction. This new method makes the effect of plastics and reconstructions to a new height. This new method dramatically improves the quality of life for buccal cancer patients. Abstract: Objective: To explore a new method of reconstruction of through-and-through cheek defects and to evaluate this method's efficacy and patient prognosis. Materials and methods: This retrospective study included 70 patients who underwent reconstruction of through-and-through cheek defects. The surgical approach, design of facial skin incisions, selection and design of flaps, postoperative quality of life and prognosis of patients were recorded and reported. Results: Postoperative quality of life gradually increased over time, and the mean scores of University of Washington Quality of Life (UW-QOL) Questionnaire was more than 80 at 1-year postoperatively. The appearance, oral competence, chewing, swallowing, speech and other oral functions were well recovered in about 90% of patients at 1-year postoperatively. Conclusion: This new idea of reconstruction before tumour resection, brings the effect of plastic and reconstructive surgery to a new height.